Taurine Protects against Postischemic Brain Injury via the Antioxidant Activity of Taurine Chloramine - Song-I Seol; Hyun Jae Kim; Eun Bi Choi; In Soon Kang; Hye-Kyung Lee; Ja-Kyeong Lee; Chaekyun Kim (MDPI AG, 2021)
Taurine is ubiquitously distributed in mammalian tissues and is highly concentrated in the heart, brain, and leukocytes. Taurine exerts neuroprotective effects in various central nervous system diseases and can suppress infarct formation in stroke. Taurine reacts with myeloperoxidase (MPO)-derived hypochlorous acid (HOCl) to produce taurine chloramine (Tau-Cl). We investigated the neuroprotective effects of taurine using a rat middle cerebral artery occlusion (MCAO) model and BV2 microglial cells. Although intranasal administration of taurine (0.5 mg/kg) had no protective effects, the same dose of Tau-Cl significantly reduced infarct volume and ameliorated neurological deficits and promoted motor function, indicating a robust neuroprotective effect of Tau-Cl. There was neutrophil infiltration in the post-MCAO brains, and the MPO produced by infiltrating neutrophils might be involved in the taurine to Tau-Cl conversion. Tau-Cl significantly increased the levels of antioxidant enzymes glutamate-cysteine ligase, heme oxygenase-1, NADPH:quinone oxidoreductase 1, and peroxiredoxin-1 in BV2 cells, whereas taurine slightly increased some of them. Antioxidant enzyme levels were increased in the post-MCAO brains, and Tau-Cl further increased the level of MCAO-induced antioxidant enzymes. These results suggest that the neutrophils infiltrate the area of ischemic injury area, where taurine is converted to Tau-Cl, thus protecting from brain injury by scavenging toxic HOCl and increasing antioxidant enzyme expression.